KANDUNGAN PROTEIN DAN SERAT KASAR AMPAS TEBU YANG DI AMONIASI MENGGUNAKAN UREA DENGAN DOSIS YANG BERBEDA - Lia Resty Fauzy; Habibah Habibah; Nursyam Andi Syarifuddin (www.ulm.ac.id, 2023)
This research was conducted to determine bagasse's crude protein and fibre content, which wasammoniated using urea at different doses. This research method used a completely randomizeddesign (CRD) with four treatments and five replications totalling 20 trials consisting of (P0)bagasse + 5% bran + 0% urea, (P1) bagasse + 5% bran + 2.5 % urea, (P2) bagasse + 5% rice bran+ 5% urea and (P3) bagasse + 5% rice bran + 7.5% urea. Analysis of crude protein and crude fibrewas carried out for seven days. Data were analyzed whit by Analysis of Variance (ANOVA)followed by Duncan's multiple range test assisted by IBM's SPSS Ver 26 software. The resultsshowed that the addition of urea at different doses had a significant effect (p<0.05) on increasingcrude protein content and decreasing crude fibre content. The use of 7.5% urea resulted in thehighest crude protein content of 22.53% and the lowest crude fibre content of 31.36%. Thisresearch needs to be continued to determine in vitro digestibility before being applied to ruminantsas animal feed ingredients.